2007
DOI: 10.1002/erv.804
|View full text |Cite
|
Sign up to set email alerts
|

The needs of carers of patients with anorexia and bulimia nervosa

Abstract: Our results suggest that carers themselves have high levels of needs which are usually not addressed in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 18 publications
3
47
1
4
Order By: Relevance
“…Further, the problem areas identified by eating disorder carers have been found to be similar to that of schizophrenia carers [14]. Eating disorder carers often identify a need for more general information about eating disorders, practical advice on the development how to cope with the illness, and sources of informal and professional support [8,9,12]. Similarly, the one quantitative study examining eating disorder carer needs found that a higher need for support from people or organizations significantly predicted negative appraisal of the caregiving situation [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the problem areas identified by eating disorder carers have been found to be similar to that of schizophrenia carers [14]. Eating disorder carers often identify a need for more general information about eating disorders, practical advice on the development how to cope with the illness, and sources of informal and professional support [8,9,12]. Similarly, the one quantitative study examining eating disorder carer needs found that a higher need for support from people or organizations significantly predicted negative appraisal of the caregiving situation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Caring for someone with an eating disorder is associated with a high level of burden [6,7] and psychological distress [8]. Qualitative [9] and quantitative [10,11] studies identify several important factors related to the experience of carer burden and psychological distress, including carer needs, expressed emotion, coping strategies and social support.…”
Section: Introductionmentioning
confidence: 99%
“…En cambio, otro estudio muestra que los cuidadores en trastornos alimentarios tienen mayores niveles de malestar y de difi cultades en su rol de cuidador comparado con cuidadores de pacientes psicóticos (Treasure et al, 2001). Por otro parte, el estudio de Graap et al (2008a) encontraron diferencias signifi cativas respecto a las características y necesidades de los familiares pertenecientes a distintos subtipos de diagnóstico de trastorno alimentario. Se encontraron puntuaciones más elevadas en el malestar psicológico medido por el GHQ-12 en padres de pacientes con AN comparada con padres de pacientes con bulimia nerviosa (BN).…”
Section: Introductionunclassified
“…Los tratamientos de los pacientes con trastornos de la conducta alimentaria (TCA) son prolongados y costosos, y un 20% de los casos se cronifi can (Morande, Celada, y Casas, 1999;Ratnasuriya, Eisler, Szmukler, y Russell, 1991). En contraste, estudios sobre los cuidadores de personas con trastornos del comportamiento alimentario han recibido menos atención científi ca aunque se han incrementado en esta última década (Highet, Thompson, y King, 2005;Kyriacou, Treasure, y Schmidt, 2008a;Kyriacou, Treasure, y Schmidt, 2008b;Monteleone, Treasure, Santonastaso, Favaro, y Brambilla, 2005;Sepulveda et al, 2009;Graap et al, 2008b;Winn et al, 2006). En un estudio sobre una amplia muestra de familias con un paciente psiquiátrico y de diferentes patologías (esquizofrenia, TCA, depresión mayor, trastor-una tendencia a la cronicidad y deterioro psicosocial.…”
Section: Introductionunclassified
“…Predictors of burden and psychological distress in unaffected family members include maladaptive coping strategies, high expressed emotion and unmet caregiver needs (Coomber & King, 2013). The burden of caregiving is also associated with lower levels of social support (Graap et al, 2008;Perkins et al, 2004;Treasure et al, 2008;Winn et al, 2004). Parents report experiencing social isolation because of their perception that they were excluded from extended family members and peers (Hillege et al, 2006).…”
Section: Differential Environmental Influences Between Siblings and Imentioning
confidence: 99%